In Vitro Antimicrobial Activity of Doripenem, a New Carbapenem - Ge, Yigong (American Society for Microbiology, 2004)
The doripenem MICs at which 90% of the tested strains were inhibited ranged from 0.03 to 1 μg/ml for 10 species of Enterobacteriaceae (n = 351), from 0.03 to 0.12 μg/ml for oxacillin-susceptible staphylococci (n = 119), from 4 to 32 μg/ml for oxacillin-resistant staphylococci (n = 64), from ≤0.008 to 0.06 μg/ml for penicillin-susceptible streptococci (n = 132), and from 1 to 4 μg/ml for penicillin-resistant streptococci (n = 51). Overall, doripenem demonstrated in vitro activity similar to that of meropenem against gram-negative pathogens and to that of imipenem against gram-positive pathogens.